BARBEKU (Barang Bekas di Sekitarku) Sebagai Alat Peraga Sederhana Untuk Meningkatkan Pemahaman Siswa Pada Materi Kapilaritas - Lilis Setyaningrum; Marmi Sudarmi; Alvama Pattiserlihun (Radiasi : Jurnal Berkala Pendidikan Fisika, 2018)
Not all schools are able to provide teaching aids as learning media because of the limited tools they have, especially in remote areas that are difficult to get tools. For schools where there is no equipment at all (there is equipment but not complete or damaged) it is necessary to procure media. This study aims to: (1) provide examples of some simple teaching aids that can be used as ideas (ideas) by teachers as learning media for facilitating learning, (2) make Learning Implementation Plans on capillary material by using simple teaching aids, (3) find out the level of students' understanding after learning using simple teaching aids in Kapilaritas material. This study used the Classroom Action Research method with the type of teacher as a researcher. In this type the teacher has a dual role as a practitioner and as a researcher. The samples used for the study were 25th-grade students of SMP Negeri 3 Tuntang as many as 25 students. Research instruments for data collection were are RPP, observation sheets of Teaching and Learning Activities (KBM), questionnaire sheets, and evaluation questions. From the observation sheet, 85.71% of students were able to attend teaching and learning activities well. From the questionnaire, as many as 92.62% of students think that the teaching aids used can show capillary events clearly, and there are / easily found in the surrounding environment. From the evaluation results, as many as 84% ​​of students scored above 70. From the study, it can be concluded that learning using teaching aids simple from used goods in the surrounding environment such as glass, axis, tissue, and cloth can show capillary events so that they can be used as learning media.